Disaster preparedness as social control. Issue 1 (2nd January 2018) - Baker, Natalie D.; Grant Ludwig, Lisa
ABSTRACT: This paper discusses research on disaster management institutions, as well as members of the vulnerable public in an area of significant seismic risk. Our main theoretical conclusion is that disaster preparedness is a problem because people do not do what they are supposed to in the ways they are told by authority figures. They have breached a social norm. The need for public preparedness is constructed as a fundamental part of management efforts, where the vulnerable public is thought of as both complacent and potentially threatening in post-disaster contexts. The authors find institutional perspectives idealize public preparedness as a major goal, but in doing so also emphasize social control. This is in contrast to public reflections that demonstrate the potential for collective self-organization and altruistic behavior when they imagine how they would respond in a disaster. The institutional need for compliance in acts of preparing is built on fear of the public and resonates with the growth of disaster management practices inspired by military structures (i.e. the Incident Command System). Here, we suggest the paradigm of preparedness needs to be re-framed to more accurately reflect the reality of public behavior during such events.